2011
DOI: 10.1530/eje-10-1113
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone status within the physiological range affects bone mass and density in healthy men at the age of peak bone mass

Abstract: Context: The hormonal factors involved in the regulation of peak bone mass (PBM) in men have not been fully investigated. Apart from gonadal steroids and somatotropic hormones, thyroid hormones are known to affect bone maturation and homeostasis and are additional candidate determinants of adult bone mass. Objective: We aimed to investigate between-subject physiological variation in free and total thyroid hormone concentrations, TSH, and thyroid binding globulin (TBG) in relation to parameters of bone mass, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
(67 reference statements)
4
38
1
Order By: Relevance
“…Similar to the current study, Murphy et al also reported an inverse correlation between fT 4 and BMD by multiple linear regression. Other studies have also demonstrated that women with higher fT 4 levels within the normal reference range have lower BMD, but they found little or no association between BMD and TSH (10,11,12,25). Interestingly, in a study from Taiwan using a similar cross-sectional design in women of comparable age to the current study, no relation was demonstrated between TSH and BMD, while the authors found a significant but weak correlation between BMD and fT 4 in postmenopausal women (11).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 73%
See 1 more Smart Citation
“…Similar to the current study, Murphy et al also reported an inverse correlation between fT 4 and BMD by multiple linear regression. Other studies have also demonstrated that women with higher fT 4 levels within the normal reference range have lower BMD, but they found little or no association between BMD and TSH (10,11,12,25). Interestingly, in a study from Taiwan using a similar cross-sectional design in women of comparable age to the current study, no relation was demonstrated between TSH and BMD, while the authors found a significant but weak correlation between BMD and fT 4 in postmenopausal women (11).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 73%
“…Only a few studies have investigated a possible effect of the fT 4 concentration in subclinical thyroid dysfunction (10,11,12), which by definition lies within the reference range. Moreover, it is possible that the subjects with subclinical hyperthyroidism and a fT 4 level in the upper normal range have more adverse clinical outcomes than the subjects with subclinical hyperthyroidism and fT 4 levels in the middle or lower reference range, or compared with euthyroid individuals (3).…”
Section: Introductionmentioning
confidence: 99%
“…The results of in vitro experiments support the observations that TSH negatively regulates osteoclastogenesis and exerts a protective effect on bone [3]. According to recent reports, variations of serum TSH within the physiological range do not greatly influence BMD and there is no correlation between bone turnover markers and TSH [4,5]. On the other hand, subclinical hyperthyroidism, and even thyroid function within the upper normal range, have been shown to affect bone density and the risk of nonvertebral fractures in postmenopausal women [6,7].…”
Section: Introductionsupporting
confidence: 82%
“…This suggests an individual set point for pituitary-thyroid axis function (1). We and others have shown that this between-subject variation in TH levels, although within the normal range, is nevertheless associated with a number of clinical parameters such as bone mass, BMI, metabolic indices, and heart rate (2,3,4,5). The physiological basis of the set point of this axis is poorly understood (6).…”
Section: Introductionmentioning
confidence: 98%